The Art of Survival: Exploring Resilience in Hilary Mantel’s Wolf Hall - Yogeshkumara M V (International Research Journal on Advanced Engineering and Management (IRJAEM), 2025)
This study focuses on the psychological complexities of resilience in Thomas Cromwell, the central character of Mantel’s historical fiction Wolf Hall (2009). Set against Tudor England’s volatile political and religious climate, the novel examines Cromwell’s rise from the blacksmith’s son to Henry VIII’s most trusted advisor. This study exemplifies Cromwell’s journey and the interplay between personal loss, adaptability, and emotional fortitude. By navigating power dynamics, betrayals, and shifting allegiances, Cromwell survives and thrives in a world dominated by hierarchical structures and moral ambiguities. Employing a psychological viewpoint, this argument explores how Mantel’s use of interior monologues and close third-person narration provides insights into Cromwell’s emotional struggles and adversity. This paper situates his resilience within broader contemporary discussions of human psychology, emphasising how Mantel reinterprets historical narratives to reflect modern understandings of survival, identity, and agency. Additionally, this study highlights how Wolf Hall transcends its historical setting to offer a timeless understanding of the human capacity for reinvention and endurance. Through Cromwell’s character, Mantel crafts a narrative that challenges the conventional portrayals of historical figures, offering a profound and empathetic exploration of resilience that resonates with the contemporary world.